Perbandingan Preloading dan Coloading Cairan Kristaloid Ringer Laktat terhadap Tekanan Darah pada Pasien Spinal Anestesi di RS Roemani Muhammadiyah Semarang - Marinda Nadila Tari; Astika Nur Rohmah; Gatot Suparmanto (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Spinal anesthesia is commonly used in surgical procedures but often leads to hypotension due to sympathetic blockade, which can seriously affect the patient's hemodynamic stability. To prevent this, the administration of lactated Ringer crystalloid fluid using preloading (before anesthesia) and coloading (during anesthesia) methods is widely implemented. This study aimed to compare the effects of preloading and coloading on blood pressure stability in patients undergoing spinal anesthesia at Roemani Muhammadiyah Semarang Hospital. A quantitative research method with a comparative observational design and cross-sectional approach was used, involving 40 patients divided equally into preloading and coloading groups. Blood pressure was measured before and after fluid administration, and data were analyzed using paired t-test and independent t-test. Results showed significant changes in blood pressure in both groups (p=0.000; p<0.05). Furthermore, the independent t-test indicated a significant difference between the two methods (p=0.019; p<0.05), with preloading proving more effective in maintaining blood pressure stability than coloading. In conclusion, there is a significant comparison between preloading and coloading of lactated Ringer crystalloid fluid on blood pressure in spinal anesthesia patients, with preloading showing a superior stabilizing effect on blood pressure.